The Factors Related to Self-Treatment Behaviors among Type 2 Diabetic Patients: Application of the Theory of Planned Behavior - Mohadese Sadri; Mahrokh Einolghozati; Majid Barati; Younes Mohammadi (Mashhad University of Medical Sciences, 2023)
Background: Diabetes is the most common and severe metabolic disease in human. Self-treatment behaviors are common problems among diabetic patients.Aim: The present study was conducted with aim to identify the factors related to self-treatment behaviors among type 2 diabetic patients based on the Theory of Planned Behavior (TPB).Method: This cross-sectional study was carried out on 381 diabetic patients referred to Hamadan Diabetes Research Center in 2019, which were recruited with a simple sampling method. The participants completed a self-administered questionnaire, including demographic characteristics and TPB constructs. Data were analyzed by SPSS software (version 18) and descriptive statistics, one-way ANOVA, Independent t-test, and Linear regression. p<0.05 was considered statistically significant.Results: The mean age of the participants was 55.69±11.45 and 68.2% of the patients were male. Also, 22.3% of participants did not refer to a specific physician to monitor the diabetes treatment. Significant differences were found in the mean score of self-treatment behaviors related to gender, dwelling, and having a specific physician (p<0.05). According to the result, the TPB construct explained 16% of the variance in the frequency of self-treatment behaviors. Attitude (β=0.227) and perceived behavior control (β=-0.110) were the best significant predictors of behavioral intention (p<0.05).Implications for Practice: The findings obtained in the present study suggest that applying TPB would be an efficient tool for predicting self-treatment behaviors among diabetic patients.